Will others approve? Effects of an injunctive norms intervention on intentions to use protective behavioral strategies during drinking games. (4th March 2022) - Stephens, Clare A. M.; Eamiello, Madison L.; Venditti, Lydia; Piibe, Aleksandra; Zamboanga, Byron L.; Reid, Allecia E.
Abstract: Background: Playing drinking games is associated with increased alcohol consumption and negative consequences. Using protective behavioral strategies while playing drinking games (e.g. alternating alcoholic and nonalcoholic drinks) may reduce consumption and consequences. We hypothesized that an injunctive norms intervention, conveying peer approval for using protective strategies during drinking games, would increase perceptions of approval for strategy use, and in turn, intentions to use protective strategies. We also expected intervention effects to be stronger for women and students who endorse social lubrication motives for playing games. Method: In all, 133 college students who had ever played drinking games reported gender and social motives for playing drinking games and were randomized to the intervention or assessment only control. Perceived injunctive norms for and intentions to use protective strategies during drinking games were assessed post-intervention. Results: Relative to control participants, intervention recipients reported greater intentions to use protective strategies during drinking games; this effect was mediated by heightened injunctive norms in the intervention group. Intervention effects did not depend on gender or social motives. Conclusions: Building on these promising findings, research is needed on whether injunctive norms interventions translate into actual use of protective strategies while playing drinking games.